Prenatal phenotypes and pregnancy outcomes of fetuses with recurrent 1q21.1 microdeletions and microduplications - Yue, Fagui; Yang, Xiao; Jiang, Yuting; Li, Shibo; Liu, Ruizhi; Zhang, Hongguo (Frontiers in Medicine, 2023)
Objective: Chromosomal 1q21.1 deletions and duplications are genomic disorders which are usually diagnosed postnatally. However, the genotype-phenotype correlations of 1q21.1 copy number variants (CNVs) during prenatal period are still not clear. This study aimed to provide a systematical summary of prenatal phenotypes for such genomic disorders. Methods: Twenty-six prenatal amniotic fluid samples diagnosed with 1q21.1 microdeletions/microduplications were obtained from pregnant women who opted for invasive prenatal testing. Karyotypic analysis and chromosomal microarray analysis (CMA) were performed for all cases simultaneously. The pregnancy outcomes and health conditions after birth for all cases were followed up. Meanwhile, prenatal cases with 1q21.1 microdeletions or microduplications in the literature were retrospectively collected. Results: Eleven pregnancies (11/8252, 0.13%) with 1q21.1 microdeletions and fifteen (15/8252, 0.18%) with 1q21.1 microduplications were identified. Among these 1q21.1 CNVs, four cases covered thrombocytopenia-absent radius (TAR) region, sixteen cases covered 1q21.1 recurrent microdeletion/microduplication region, and six cases covered all regions mentioned above. The prenatal abnormal ultrasound findings were recorded in four participants with 1q21.1 deletions and seven participants with 1q21.1 duplications. Finally, three cases with 1q21.1 deletions and five with 1q21.1 duplications terminated their pregnancies. Conclusion: 1q21.1 microdeletions were associated with increased nuchal translucency (NT), anomalies of urinary system and cardiovascular abnormalities, and 1q21.1 microduplications were correlated with cardiovascular malformations, nasal bone dysplasia and increased NT in prenatal setting. In addition, cerebral ventriculomegaly might be correlated with 1q21.1 microduplications. Considering the variable expressivity and incomplete penetrance of 1q21.1 CNVs, long term follow up after birth should be carried out for these cases.